ALTERNATIF KONTRUKSI TITIK NAGEL - Suryani, Indah; ', Mashadi; Natsir, M. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This paper discusses the alternative construction of Nagel point, that is the point formedby intersection of three vertices of a triangle which is connected to the points oftangency of the excircle with the opposite sides. This alternative constructionhas beenshown to pass through the incircle. Then, this paper also discusses about outer Nagelpoint(semi Nagel point) and prove the concurrence of the Nagel point.